Examining a Ripple Effect: Do Spouses’ Behavior Changes Predict Each Other’s Weight Loss? - Anna E. Schierberl Scherr; Kimberly J. McClure Brenchley; Amy A. Gorin (Journal of Obesity)
Background. Including spouses in obesity treatment has been found to promote weight loss. We assessed whether spouses’ diet and activity changes impacted each other’s weight loss when both members attended an active weight loss program (TOGETHER) or only the primary participant attended treatment (ALONE). Methods. Heterosexual couples (N=132) enrolled in an 18-month randomized controlled weight loss trial were weighed and completed measures of dietary intake and physical activity at baseline and 6 months. We conducted dyadic data analyses using the Actor-Partner Interdependence Model. Results. Participants’ weight loss was not predicted by their partners’ behavior changes. However, partners’ weight loss was predicted by their participants’ changes in calorie and fat intake. When partners were coupled with a participant who did not reduce their own calorie and fat intake as much, these partners had higher weight loss when treated in the TOGETHER group but lower weight loss when they were untreated in the ALONE group. There were no reciprocal effects found with physical activity changes. Conclusions. Direct treatment had the greatest impact on participants and partners who were treated. Untreated partners’ weight losses were positively impacted by their spouses’ dietary changes, suggesting a ripple effect from treated spouses to their untreated partners.